Annual Prediction Output of an RADTIRC-PV Module - Freier, Daria; Muhammad-Sukki, Firdaus; Abu-Bakar, Siti Hawa; Ramirez-Iniguez, Roberto; Munir, Abu Bakar; Mohd Yasin, Siti Hajar; Bani, Nurul Aini; Mas'ud, Abdullahi Abubakar; Ardila-Rey, Jorge Alfredo; Karim, Mohammad Ershadul (MDPI, 2018)
The number of solar photovoltaic (PV) installations has been increasing worldwide but the high capital cost of installation continues to be the main challenge, particularly in many developing countries. The solar concentrator, a device that focuses the sunlight onto a small area, has the potential to minimize the use of expensive PV material while maintaining the system's performance, ultimately bringing down its overall cost. This study aims to predict the annual electrical output of a specific concentrator design called the rotationally asymmetrical dielectric totally internally reflecting concentrator (RADTIRC). The aforementioned design is assumed to be installed in Berlin/Brandenburg, Germany. First, a short review of concentrators is provided. Next, a description of the RADTIRC and the previous research that revolved around it are provided. Afterwards, the key parameters that are needed to determine the annual electrical output of the RADTIRC are explained before presenting the results of the simulations. It was found that the yearly energy yield was increased by a factor of 2.29 when the RADTIRC-PV module was used when compared with the non-concentrating PV module.